Anisakis spp. in toothed and baleen whales from Japanese waters with notes on their potential role as biological tags. (February 2021) - Gomes, Tiago Leandro; Quiazon, Karl Marx; Kotake, Maho; Fujise, Yoshihiro; Ohizumi, Hiroshi; Itoh, Naoki; Yoshinaga, Tomoyoshi
Abstract: In this study, Anisakis nematodes isolated from toothed and baleen whales from localities around Japan were molecularly (PCR-RFLP) identified. In Wakayama, common bottlenose dolphins ( Tursiops truncatus ) were infected with A. simplex sensu stricto (s.s.), A. typica and A. pegreffii, while A. typica was the only species found in pantropical spotted dolphin ( Stenella attenuata ) and striped dolphin ( S. coeruleoalba ). Offshore common minke whales ( Balaenoptera acutorostrata ) and sei whales ( B. borealis ) were almost exclusively infected with A. simplex s.s.. However, in common minke whales from two Hokkaido localities, mature worms mostly consisted of A. simplex s.s. in some individuals and of A. pegreffii in others, but immature worms were mainly A. simplex s.s.. Gross and histopathological examination on gastric mucosa attached by anisakids resulted in mild and superficial reactions by the two baleen whale species in contrast to severe inflammatory reaction associated with ulcer formations by common bottlenose dolphin. Host specificity and adaptability of Anisakis spp. in these baleen and toothed whales were discussed from the points of view of adult worm size, worm population and pathological reactions by hosts. Interestingly, most of the common minke whales predominantly harboring mature A. pegreffii adults belonged to the Yellow Sea – East China Sea stock (J stock), which migrates through the Sea of Japan, whereas most of those mainly parasitized by mature A. simplex s.s. adults were from the Okhotsk Sea – West Pacific stock (O stock), mostly inhabiting the Pacific side, suggesting that these sibling species may have utility as biological tags to differentiate whale stocks. These results represent the first definitive host records for A. pegreffi in the Northwestern Pacific Ocean.